If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 24 = 2x + -36 Reorder the terms: 24 + 4x = 2x + -36 Reorder the terms: 24 + 4x = -36 + 2x Solving 24 + 4x = -36 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 24 + 4x + -2x = -36 + 2x + -2x Combine like terms: 4x + -2x = 2x 24 + 2x = -36 + 2x + -2x Combine like terms: 2x + -2x = 0 24 + 2x = -36 + 0 24 + 2x = -36 Add '-24' to each side of the equation. 24 + -24 + 2x = -36 + -24 Combine like terms: 24 + -24 = 0 0 + 2x = -36 + -24 2x = -36 + -24 Combine like terms: -36 + -24 = -60 2x = -60 Divide each side by '2'. x = -30 Simplifying x = -30
| M^2+8m+13=0 | | -8k-4k=0 | | -x+6x-82=43 | | (2x-16)=(x+16) | | 9x-4+2x-6=5x-2+3x+5 | | 1/25^2 | | 116+5x-28+64+3x=360 | | x^4-8x^3+16x^2+8x-16=0 | | (7Y+5)-(3+6Y)=12 | | -4y-12=2y+12 | | 4/5×75 | | -2(5m-4)-3(3m+1)= | | (5/8)*4 | | 7b+5b=-12 | | (5/8)4 | | 0.6x-11=1.1x-16 | | 10a+b=3ab | | 2(4p+6)-4(p+1)= | | (5x/8)4 | | mn=2m-5n | | f(x)=2x^2-12x+19 | | 3-11x=36 | | 5-3(b+2)=2b+7-(b-2) | | 6x+1y=-29y | | 9t+2=20 | | 22+2m=37+6+m | | -9x+y=-6 | | 5y^2+15y= | | 5*29n=215 | | 3(7-2x)=5(4-2x) | | 2+14x=9x-8 | | -3=13-2x |